Public Perceptions of PPPK and PNS in Indonesia through Social Media Discussions - Rostina Rostina (Journal of Research and Development on Public Policy, 2026)
Public sector reform in Indonesia has introduced a dual employment system within the Aparatur Sipil Negara (ASN), consisting of permanent civil servants (Pegawai Negeri Sipil/PNS) and contractual civil servants (Pegawai Pemerintah dengan Perjanjian Kerja/PPPK). Although this policy aims to improve workforce flexibility and address staffing needs, it has generated various public responses related to fairness, job security, and professional recognition. These responses are increasingly expressed through social media which functions as an important space for public discussion and opinion formation. This study analyzes public perceptions of PNS and PPPK in Indonesia through social media discussions. A qualitative content analysis method was applied to publicly available posts and comments from X (formerly Twitter), Instagram, and TikTok during the period 2024–2025. Individual posts and comments were used as units of analysis and coded thematically to identify dominant narratives and recurring issues. PPPK employees are often perceived as having lower job security and social status, while PNS employees are associated with stability and prestige. At the same time, many social media users express criticism toward government policy implementation, particularly regarding financial capacity, transparency, and perceived favoritism. Social comparison between PPPK and PNS further strengthens stigma and symbolic inequality within the civil service system. This study concludes that public sector reform should be understood not only as an administrative change but also as a social issue shaped by public perceptions. Analyzing social media discourse provides valuable insights for policymakers in improving communication strategies, policy implementation, and public trust in ASN reforms.